2014
DOI: 10.1007/s10875-014-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Natural Killer T Cells are Reduced in Hereditary Hemochromatosis Patients

Abstract: Altogether, our results demonstrate that HH patients have reduced numbers of iNKT cells and that these are influenced by iron overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Recently, a study comparing HH patients and control individuals reported reduced numbers of circulating iNKT in HH patients . Untreated patients had more prominent defects in iNKT cells that were reflected in levels of serum ferritin and Tf saturation.…”
Section: Hfe Functions In the Immune Systemmentioning
confidence: 99%
“…Recently, a study comparing HH patients and control individuals reported reduced numbers of circulating iNKT in HH patients . Untreated patients had more prominent defects in iNKT cells that were reflected in levels of serum ferritin and Tf saturation.…”
Section: Hfe Functions In the Immune Systemmentioning
confidence: 99%
“…Consequently, increased iron levels in the blood stream are observed [1,4,5]. The altered immunological status observed in HFE-associated HH patients is mainly due to iron overload, leading, for example, to lower levels of circulating invariant natural killer cells [20] or lower levels of cytokine production in macrophages [21]. In C282Y HH patients, the lower levels of expression of MHC class I molecules shown in peripheral mononuclear cells have been attributed to impaired intracellular trafficking due to HFE failing to bind to β2-microglobulin [22,23].…”
Section: Introductionmentioning
confidence: 99%